Analisis Minat ASN Membayar Zakat Pada Badan Amil Zakat Nasional Kota Semarang - Lintang Kalatidha; Banatul Hayati (ITB AAS INDONESIA Surakarta, 2022)
The research objective is to analyze the influence of religiosity, income level, belief, and knowledge partially and simultaneously on the interest of ASN to pay zakat at BAZNAS Semarang City. The data used is primary data collected through interviews with 100 ASN respondents who pay zakat at BAZNAS Semarang city. The data analysis method used in this research is multiple regression. The results showed that partially religiosity, knowledge and belief had a significant positive effect, while income level was not significant in influencing muzzaki paying zakat. Simultaneously, religiosity, income, knowledge, and belief have a significant effect on ASN interest in paying zakat at BAZNAS Semarang city. Keywords : interest, zakat, religiosity, income level, knowledge of belief